2003
DOI: 10.1159/000074074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Corticosteroids and Nonsteroidal Anti-Inflammatory Drugs on Prostaglandin E<sub>2</sub>-Induced Aqueous Flare Elevation in Pigmented Rabbits

Abstract: We evaluated the effects of anti-inflammatory potency of corticosteroids and nonsteroidal anti-inflammatory drugs on prostaglandin E2 (PGE2)-induced aqueous flare elevation in pigmented rabbits. Transcorneal diffusion of PGE2, 25 µg/ml (7.09 × 10–2 mmol/l), with the use of a glass cylinder was achieved to produce aqueous flare elevation. Anti-inflammatory drugs were topically administered once before PGE2 application. Aqueous flare was measured with a lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…It is possible that the corneal penetration of these compounds may be poor. In our pre- vious study, diclofenac sodium 0.1% instilled topically 1 h before PGE 2 application and dexamethasone sodium diphosphate 0.1% instilled topically 6 h before PGE 2 application showed maximally inhibitory effects on aqueous flare elevation [3,4]. In the present study, diclofenac sodium injected 30 min before PGE 2 application and dexamethasone sodium diphosphate injected 300 min before PGE 2 application showed maximally inhibitory effects on aqueous flare elevation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It is possible that the corneal penetration of these compounds may be poor. In our pre- vious study, diclofenac sodium 0.1% instilled topically 1 h before PGE 2 application and dexamethasone sodium diphosphate 0.1% instilled topically 6 h before PGE 2 application showed maximally inhibitory effects on aqueous flare elevation [3,4]. In the present study, diclofenac sodium injected 30 min before PGE 2 application and dexamethasone sodium diphosphate injected 300 min before PGE 2 application showed maximally inhibitory effects on aqueous flare elevation.…”
Section: Discussionsupporting
confidence: 55%
“…A glass cylinder was attached to the cornea to avoid transconjunctival diffusion. We have also reported that topical instillation of corticosteroids (betamethasone phosphate 0.1%, dexamethasone sodium phosphate 0.1% and fluorometholone 0.1%) 6 h before PGE 2 application inhibited PGE 2 -induced aqueous flare elevation and that topical instillation of nonsteroidal anti-inflammatory drugs (NSAIDs; diclofenac sodium 0.1%, bromfenac sodium 0.1% and pranoprofen 0.1%) 1 h before PGE 2 application suppressed flare elevation [3,4].…”
Section: Introductionmentioning
confidence: 89%
“…In addition, the NSAID (tepoxalin) used in that study was administered one hour before paracentesis (GILMOUR & LEHENBAUER, 2006). HAYASAKA et al (2003) and ABE et al (2004) demonstrated that topical or intravenous administration of nonsteroidal antiinflammatory drugs are able to suppress the protein influx to aqueous humor, only when used one hour and a half before the blood-aqueous barrier breakdown.…”
Section: Discussionmentioning
confidence: 97%
“…Nonsteroidal anti-inflammatory drugs suppress the protein influx to aqueous humor, after one hour and a half, whereas corticosteroids may need six hours after administration to show action by inhibitory effects on expression of the messenger RNAencoding cyclooxygenases-related protein (HAYASAKA et al, 2003;ABE et al, 2004). The reduction of only 27% in protein levels, contrasts the observations of a previous study, which proved that topical flurbiprofen, diclofenac, and suprofen were effective at preventing blood-aqueous barrier disruption after paracentesis in dogs (WARD, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that 0.1% bromfenac sodium eye drops are as safe and effective for the treatment of allergic conjunctivitis [21]. Although it has been reported that bromfenac sodium has the strongest potency in inhibiting PGE 2 -induced aqueous flare among NSAID [22], its role in the treatment of ocular allergic disorders has not been reported in experimental or clinical studies. The aim of this study was to evaluate the efficacy and safety of long-term management with bromfenac sodium eye drops in combination with corticosteroid and anti-allergic eye drops in patients affected by VKC.…”
Section: Introductionmentioning
confidence: 99%